Barriers to radiotherapy access at the University College Hospital in Ibadan, Nigeria - Chidinma P. Anakwenze; Atara Ntekim; Bruce Trock; Iyobosa B. Uwadiae; Brandi R. Page (Clinical and Translational Radiation Oncology, 2017)
Introduction: Nigeria has the biggest gap between radiotherapy availability and need, with one machine per 19.4 million people, compared to one machine per 250,000 people in high-income countries. This study aims to identify its patient-level barriers to radiotherapy access. Material and methods: This was a cross sectional study consisting of patient questionnaires (n = 50) conducted in January 2016 to assess patient demographics, types of cancers seen, barriers to receiving radiotherapy, health beliefs and practices, and factors leading to treatment delay. Results: Eighty percent of patients could not afford radiotherapy without financial assistance and only 6% of the patients had federal insurance, which did not cover radiotherapy services. Of the patients who had completed radiotherapy treatment, 91.3% had experienced treatment delay or often cancellation due to healthcare worker strike, power failure, machine breakdown, or prolonged wait time. The timeliness of a patient’s radiotherapy care correlated with their employment status and distance from radiotherapy center (p < 0.05). Conclusions: Barriers to care at a radiotherapy center in a low- and middle-income country (LMIC) have previously not been well characterized. These findings can be used to inform efforts to expand the availability of radiotherapy and improve current treatment capacity in Nigeria and in other LMICs.